2021
DOI: 10.1088/1755-1315/761/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the electric shock on embryonic development and neurophysiological traits in the chick’s embryo

Abstract: The objective of this study was to investigate the impact of stimulating the embryo during the dormancy in the incubation period. 450 eggs (Ross 308) were allocated in four treatments each three replicates. The treatments were as follow: T1 control (without shock), T2 Shocked (40) Millivolts (mV), T3 Shocked (50) (mV), T4 Shocked (75) (mV). A different voltage device was used to shock the egg, after marking the eggs with a line of iron filings to ensure electrical conductivity, eggs were shocked at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The results were consistent with the findings of (9,10) in the difference in oat varieties in the number of Panicles m -2 . The availability of conditions helped to increase the number of Panicles m -2 when adding amino acid, which is consistent with (11)(12)(13), who pointed to the effect of amino acid in increasing the number of Panicles m -2 for wheat crops.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results were consistent with the findings of (9,10) in the difference in oat varieties in the number of Panicles m -2 . The availability of conditions helped to increase the number of Panicles m -2 when adding amino acid, which is consistent with (11)(12)(13), who pointed to the effect of amino acid in increasing the number of Panicles m -2 for wheat crops.…”
Section: Discussionsupporting
confidence: 92%
“…In Table 3 we note the effect of ethylene gas on the number of grains in Panicle, this is consistent with (14,16) of the moral effect of different ethylene gas compositions in the number of grains in spike for wheat. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), they explained that there is an increase in grain yield for barley, wheat and oat crop when the concentration of medium ethylene gas but the grain product decreases at high concentration. Moreover, (15) pointed out that the harvest index values in the oat crop differed by varieties and genetic composition.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the components of good yield are directly related to the increase in indicators of good vegetative growth, the addition of humic acid improved the vegetative growth, by the activation of vital processes and the consequent increase in nitrogen absorption and increase in the number and fullness of the pods, which indicates a good metabolism in the leaves and the transfer of these products to the seeds, or, the reason may be that humic acids contain amino acids or proteins. The plant benefits directly from it, and this is reflected in the increase in the weight of the seeds 16 , this result was consistent with the findings of (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…The present study result regarding novel Iraqi summary studies shows the ROC curve yields low sensitivity of CA153, merely 22.47% 18 . The same line with a new study in 2021 showed that the low value of the sensitivity of CA15-3 serum marker in BC patients was only (59.06% ) 24 .…”
Section: Discussionmentioning
confidence: 52%
“…Diagnostic accuracy and AUC of both circulation biomarkers. sensitivity and specificity of rel-ative expression of circulating miRNA-21 in the BC patients compared with healthy control group 17,18 . Their agreement with the Iranian study showed higher sensitivity and specificity values for microRNA-21 19 .…”
Section: Discussionmentioning
confidence: 99%